Transforming Entrepreneurship Education in Higher Education: Experiential, Collaborative, and Ecosystem-Based Perspectives - Nur Hidayah; Dwi Sulisworo; Hendro Widodo (Journal of Pedagogy and Education Science, 2026)
Entrepreneurship education has become a strategic priority in higher education institutions in response to rapid economic transformation and the growing demand for innovative human resources. This study aims to synthesize and categorize contemporary models of entrepreneurship learning to identify dominant pedagogical patterns and strategic directions for implementation. Using a qualitative literature review approach, thirty empirical and conceptual studies were analyzed to examine their learning models, findings, and recommendations. The analysis reveals four major thematic clusters. First, experiential and practice-based models (such as Teaching Factory, project-based learning, production-based training, and experiential-reflective frameworks) emphasize authentic engagement and real-world business simulation to develop entrepreneurial competence and mindset. Second, curriculum integration and institutional ecosystem support highlight the importance of structured learning pathways, policy alignment, and industry collaboration. Third, social and collaborative approaches underscore entrepreneurship as a socially constructed process shaped by teamwork, mentorship, community engagement, and networks. Fourth, innovation-driven and context-responsive models integrate digital technologies, game-based learning, and culturally grounded approaches to enhance relevance and adaptability. The findings indicate that effective entrepreneurship education requires a holistic ecosystem that integrates experiential pedagogy, institutional commitment, collaborative processes, and technological innovation. Successful implementation depends on curriculum coherence, qualified educators, adequate infrastructure, and continuous evaluation mechanisms. This study contributes to the theoretical and practical development of entrepreneurship education by offering an integrated framework that supports the cultivation of an entrepreneurial mindset, competence, and sustainable societal impact.